CONSCIENCE AND WILL TO POWER: A PHENOMENOLOGICAL RECONSTRUCTION (Revista Kriterion, 2025)
This essay argues for an interpretation of Nietzsche’s concept of conscience (Gewissen) based on a phenomenological reconstruction of its characteristics, as indicated by texts in which Nietzsche attempts to describe experiences related to conscience. From this point of view, conscience plays an essentially cognitive role, in the sense of being an opening to a dimension of preconscious experiences, especially listening, strangeness, love, freedom and time, that yield epistemological and ontological value. These varied experiences reveal conscience as constituted by a myriad of nuances rooted in three basic modes, corresponding to the threefold typology of the slave, the noble and the priest. They also form the basis for a consideration of the role of consciousness (Bewusstsein) in cognition, as the modalities of conscience mobilize human intellectual capability according to different measures and limits. Lastly, the analysis of conscience provides a foundation for a phenomenological reconstruction of the concept of will to power, characterized primarily by the possibility of human freedom in the face of the power of time and secondarily by the potential for an analogical application of the concept as a heuristic principle of calculability.